A new economy the changing role of innovation and information technology in growth. (Paris Organisation for Economic Co-operation and Development, 2000)
What is driving recent growth in OECD countries? Why is it that their levels of GDP per capita are no longer converging? Why is it that some countries, operating at the technological frontier, where advances are difficult, appear to be widening the ga p? Whether or not it is appropriate to speak of a "new economy", innovation and technology play crucial roles. This study shows that success requires not some silver bullet, but a range of complementary factors that support the innovation-intensive growth exemplified by new information and communication technologies such as the Internet.
FOREWORD; TABLE OF CONTENTS; The OECD growth project; EXECUTIVE SUMMARY; INTRODUCTION; Chapter 1 PATTERNS OF ECONOMIC GROWTH IN OECD COUNTRIES; Chapter 2 THE CHANGING ROLE OF INNOVATION IN GROWTH PERFORMANCE; Chapter 3 THE ROLE OF INFORMATION AND COMM UNICATIONS TECHNOLOGY IN GROWTH PERFORMANCE; Chapter 4 POLICIES THAT SUPPORT GROWTH BASED ON INNOVATION AND INFORMATION TECHNOLOGY; NOTES; BIBLIOGRAPHY.
Includes bibliographical references (p. 85-92).
Keywords: Economics -- Innovation; Electronic books